Marx’s concept of the working class and some trends in the development of capitalism - Iñigo Carrera, Nicolas (2013)
The purpose of this article is not to present a new theoretical argument, but to recover Marx's concept of the working class1 and show its pertinence to account for the most important tendencies in the present capitalist phase. Therefore, the first part of this article deals with Marx's concept of the working class, which is not restricted to factory workers, though, at the same time, distinguishes them from other workers exploited by capital. The second part deals with some tendencies pointed out by Marx and later Marxists: the decreasing rate of rural and agricultural Population and the absolute and/or relative increase of proletarians, of the non-productive population and of the surplus population. Finally it analyses these tendencies in the Argentinean case.